Identification of Founding Accessions and Patterns of Relatedness and Inbreeding Derived from Historical Pedigree Data in a White Clover Germplasm Collection in New Zealand. Issue 5 (5th September 2019) - Egan, Lucy M.; Hofmann, Rainer W.; Barrett, Brent A.; Ghamkhar, Kioumars; Hoyos‐Villegas, Valerio
Abstract : Pedigrees provide suitable input for tracking breeding crosses and monitor plants and animal populations. Pedigree analysis is an essential tool to visualize and describe population structure and genetic diversity. Pasture plant breeding relies on a range of strategies from closed system recurrent selection using elite cultivars to diversity‐focused programs using ecotypes and wild germplasm as parents. There is currently no published pedigree analysis of white clover ( Trifolium repens L.), despite over a century of breeding efforts in New Zealand. A pedigree map was constructed for white clover germplasm stored in the Margot Forde Germplasm Centre located in Palmerston North, New Zealand. Inbreeding and kinship coefficients and the effective number of founders through time were estimated to assess genetic relatedness in the reference population. A total of 15, 265 accessions were included in the map. The maximum number of traced generations was 15, and the mean completeness of parentage for the reference population was 72%. The mean number of offspring was 5.14. The origin of founding and introduced accessions was assessed. The effective number of founders was 175.68 or 17.5% of the total number of reference founders. Founding accessions and influencing ancestors were identified. One of the earliest parental accessions identified was 'North Canterbury Type I' from 1941. Relatedness was determined using the k coefficient, with k = 1 as complete relatedness. The overall mean relatedness was k = 0.002. Overall mean inbreeding level was 0.39%. Relatedness and inbreeding coefficients revealed distinct germplasm pools formed across time that are of interest to pre‐breeding efforts.